The Fetal Posterior Fossa on Prenatal Ultrasound Imaging: Normal Longitudinal Development and Posterior Fossa Anomalies - Pertl, Barbara; Eder, Sophie; Stern, Christina; Verheyen, Sarah (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Fetal neurosonography and the assessment of the posterior fossa have gained in importance during the last 2 decades primarily due to the development of high-resolution ultrasound probes and the introduction of 3 D sonography. The anatomical development of the posterior fossa can be visualized well with the newest ultrasound technologies. This allows better knowledge of the anatomical structures and helps with understanding of the development of malformations of the posterior fossa. In this article the longitudinal development of the posterior fossa structures will be reviewed. The embryologic description will be compared with ultrasound descriptions. These embryologic and anatomic illustrations form the basis for the screening and diagnosis of malformations of the posterior fossa. During the first trimester, screening for open spina bifida as well as cystic malformations of the posterior fossa is possible. In the second and third trimester, malformations of the posterior fossa can be subdivided into 3 groups: fluid accumulation in the posterior fossa (Dandy-Walker malformation, Blake’s pouch cyst, mega cisterna magna, arachnoid cyst, vermian hypoplasia), decreased cerebellar biometrics (volume) (cerebellar hypoplasia, pontocerebellar hypoplasia) and suspicious cerebellar anatomy (Arnold-Chiari malformation, rhombencephalosynapsis, Joubert syndrome). This algorithm, in combination with knowledge of normal development, facilitates the diagnostic workup of malformations of the posterior fossa.Die fetale Neurosonografie und damit auch die sonografische Beurteilung der Strukturen der Fossa posterior haben in den letzten beiden Jahrzehnten durch den Einsatz hochauflösender Ultraschallsonden und des 3D-Ultraschalls eine besondere Bedeutung erlangt. Durch die neuen Ultraschalltechnologien kann die embryologische Entwicklung der Fossa-posterior-Strukturen nachvollzogen werden. Dies erleichtert die Kenntnis der anatomischen Strukturen und trägt zum Verständnis für die Entstehung von Fehlbildungen der Fossa posterior bei. In der folgenden Übersichtsarbeit wird die longitudinale Entwicklung der Fossa-posterior-Strukturen dargestellt. Dabei wird die embryologische Beschreibung mit der Darstellung im Ultraschall verglichen. Dieses embryologische und anatomische Wissen bildet die Grundlage für das Screening und die Diagnose von Veränderungen und Fehlbildungen der Fossa posterior. Im Ersttrimester ist ein Screening für Spina bifida aperta und zystische Fehlbildungen der Fossa posterior möglich. Im 2. und 3. Trimester können die Fehlbildungen der Fossa posterior in 3 Kategorien unterteilt werden: Fehlbildungen mit vermehrter Flüssigkeit in der Fossa posterior (Dandy-Walker-Malformation, Blakes-pouch-Zyste, Megacisterna magna, Arachnoidalzyste, Vermishypoplasie), Fehlbildungen mit verminderter Biometrie bzw. vermindertem Volumen bei „überwiegend“ normaler Anatomie des Zerebellums (zerebelläre Hypoplasie, pontozerebelläre Hypoplasie) und Fehlbildungen mit strukturell verändertem Zerebellum (Arnold-Chiari-Malformation, Rhombenzephalosynapsis, Joubert-Syndrom). Dieser Algorithmus und das Verständnis der normalen Entwicklung ermöglichen ein systematisches Aufarbeiten der Fehlbildungen der Fossa posterior.